2011
DOI: 10.1128/iai.00854-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of Defensins in Corneal Epithelial Barrier Function against Pseudomonas aeruginosa Traversal

Abstract: Studies have shown that epithelium-expressed antimicrobial peptides (AMPs), e.g., ␤-defensins, play a role in clearing bacteria from mouse corneas already infected with Pseudomonas aeruginosa. Less is known about the role of AMPs in allowing the cornea to resist infection when healthy. We previously reported that contact lens exposure, a major cause of P. aeruginosa keratitis, can inhibit the upregulation of human ␤-defensin 2 (hBD-2) by corneal epithelial cells in response to P. aeruginosa antigens in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 58 publications
4
69
0
2
Order By: Relevance
“…When blotting was followed by 1 h of EGTA treatment (100 mM in phosphate-buffered saline [PBS]), the bacteria could traverse the epithelium all the way to the underlying basal lamina (46). Using gene knockout mice, we have found that MyD88 is important for protecting the corneal epithelium against both adhesion and subsequent traversal (47) and that mBD3, the mouse equivalent of human hBD2 and a MyD88-dependent factor (51,52), is involved in this protective effect (49). We further showed that these novel methods for studying traversal of in situ-grown corneal epithelium could be adapted for ex vivo use, which allows exclusion of tear fluid and infiltrating phagocytic responses when desirable.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…When blotting was followed by 1 h of EGTA treatment (100 mM in phosphate-buffered saline [PBS]), the bacteria could traverse the epithelium all the way to the underlying basal lamina (46). Using gene knockout mice, we have found that MyD88 is important for protecting the corneal epithelium against both adhesion and subsequent traversal (47) and that mBD3, the mouse equivalent of human hBD2 and a MyD88-dependent factor (51,52), is involved in this protective effect (49). We further showed that these novel methods for studying traversal of in situ-grown corneal epithelium could be adapted for ex vivo use, which allows exclusion of tear fluid and infiltrating phagocytic responses when desirable.…”
mentioning
confidence: 98%
“…The susceptibility of MyD88 Ϫ/Ϫ corneas to ExsA-independent traversal led us to investigate if MyD88 deficiency impaired antimicrobial activity of the corneal epithelium. Our choice to focus on antimicrobial activity, rather than other potential defense factors, was based on our earlier discoveries that corneally expressed antimicrobials (including mBD3 and keratin-derived antimicrobial peptides [KDAMPs]) contribute to maintaining the corneal epithelial barrier against P. aeruginosa (49,59). Thus, the corneal epithelium of normal healthy wild-type and MyD88…”
Section: Traversal Of Myd88mentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, even large inocula of potentially pathogenic bacteria are rapidly cleared from the ocular surface when it is healthy (10)(11)(12). Various antimicrobial peptides are expressed at ocular, and other, surfaces of humans and animals.…”
Section: Introductionmentioning
confidence: 99%
“…α-HD обладают широким спектром антибактери-альной активности в отношении как грамположи-тельных, так и грамотрицательных микроорганиз-мов, а также вирусов [5,12] Кроме названных микробных агентов, β-HD-3 действует бактерицидно в отношении Streptococcus pyogenes, S. aureus, включая мультирезистентные штаммы S. aureus, и даже vancomycin-резистентный Enterococcus faecium [13][14][15]. Активность β-HD-4 в отношении P. aeruginosa более выражена, чем у дру-гих молекул HD [8].…”
Section: обзорыunclassified